(untitled) (American Journal of Technology and Applied Sciences, 2025)
This article is intended for the production of currently relevant mixed-composition suit fabrics and describes the wide application of this technology to manufacturing enterprises throughout our Republic and the possibility of increasing economic efficiency and producing quality products.